Indigenous cellulolytic aerobic and facultative anaerobic bacterial community enhanced the composting of rice straw and chicken manure with biochar addition - Mohd Zainudin, Mohd Huzairi; Singam, Jamuna Thurai; Sazili, Awis Qurni; Shirai, Yoshihito; Hassan, Mohd Ali (Nature Publishing Group, 2022)
Microbial degradation of organic matters is crucial during the composting process. In this study, the enhancement of the composting of rice straw and chicken manure with biochar was evaluated by investigating the indigenous cellulolytic bacterial community structure during the composting process. Compared with control treatment, composting with biochar recorded higher temperature (74 °C), longer thermophilic phase (> 50 °C for 18 days) and reduced carbon (19%) with considerable micro- and macronutrients content. The bacterial community succession showed that composting with biochar was dominated by the cellulolytic Thermobifida and Nocardiopsis genera, which play an important role in lignocellulose degradation. Twenty-three cellulolytic bacterial strains were successfully isolated at different phases of the composting with biochar. The 16S rRNA gene sequencing similarity showed that they were related to Bacillus licheniformis, Bacillus subtilis, Bacillus aerius, and Bacillus haynesii, which were known as cellulolytic bacteria and generally involved in lignocellulose degradation. Of these isolated bacteria, Bacillus licheniformis, a facultative anaerobe, was the major bacterial strain isolated and demonstrated higher cellulase activities. The increase in temperature and reduction of carbon during the composting with biochar in this study can thus be attributed to the existence of these cellulolytic bacteria identified.